Paradox of online and physical lectures: charting a way forward - Emmanuel O. Fabinu; Akpezi Benjamin Etobro (Konselor, 2021)
The wave of COVID-19 pandemic brought in a paradigm shift from the traditional method of physical or face-to-face to online lectures and in some cases e-assessments. This paper focused on the impact of online lectures and e-assessments in the advent of COVID-19. Two research questions and three null hypotheses guided the study. A two-part, self-developed instrument was used in the collection of data. Results showed that majority of the students preferred online classes to face-to-face classroom interaction Furthermore, findings showed that there were no significant effects of location, sex and possession of Android phones on the combined dependent variable of modes of assessment, F(2, 233) = 0.158,p = 0.854; Wilks' Lambda = 0.999; partial η2 = 0.001; F(2, 233) = 0.901,p = 0.408; Wilks' Lambda = 0.99; partial η2 = 0.008 and F(4, 468) = 0.374,p = 0.827; Wilks' Lambda = 0.99; partial η2 = 0.003, respectively. Recommendations were made.